Modern diagnosis and treatment of papillary thyroid cancer - Bardychevskyi , Dmytro; Yuzvenko , Violetta; Tovkai , Oleksandr (The Ukrainian Scientific Medical Youth Journal, 2023)
thyroid cancer is the most common malignant tumor of the endocrine glands, accounting for 1% of all cases of malignant neoplasms. According to the National Cancer Registry, 24,626 patients with thyroid cancer were identified in Ukraine for the period from 2014 to 2021, of which 4,556 were men (18.5%) and 20,070 were women (81.5%). Treatment of papillary thyroid cancer combines three methods: surgery, the use of radioiodine therapy, and hormone replacement therapy with levothyroxine drugs. The aim of this work, based on the example of a clinical case, was to analyze the patient's route, methods of diagnosis, and treatment of a thyroid neoplasm in accordance with current guidelines and recommendations. This clinical case highlights the importance of early diagnosis of TG diseases, namely papillary thyroid cancer. The patient turned to the clinic of the Ukrainian Scientific and Practical Center for Endocrine Surgery, Transplantation of Endocrine Organs and Tissues of MoH of Ukraine with complaints of an increase in the front surface of the neck and deterioration of the general condition for a long time. After analyzing the complaints, the patient was sent for a comprehensive examination, where an ultrasound of the TG revealed a mass, cytological examination confirmed a thyroid papillary cancer, grade 6. After undergoing preparation, the patient was referred for surgical intervention, namely extrafascial thyroidectomy. Combined treatment was carried out (operative intervention and treatment with the drug I131), and a suppressive dose of levothyroxine was prescribed, followed by dose correction and dynamic supervision by an endocrinologist. The described clinical case testifies to the high quality of diagnosis and treatment of a patient with thyroid papillary cancer in the conditions of a highly specialized endocrinological center. This approach fully meets the international requirements for the treatment of thyroid cancer. Despite the difficult epidemiological situation in Ukraine and the state of war, the patient was promptly referred to the Ukrainian Scientific and Practical Center for Endocrine Surgery, Transplantation of Endocrine Organs and Tissues, where she received the necessary assistance in full.